(untitled) (African Journal of Biomedical Research, 2021)
Head and Neck Cancer (HNC) are the seventh leading cancer by incidence worldwide (1). It comprises mostly of head and neck squamous cell carcinoma (HNSCC) which develops in the mucous membrane of several locations comprising; mouth, throat, larynx, nose and sinuses, and despite recent therapeutic innovation, the five-year overall survival remains at 50% (2). In 2012, the worldwide burden of HNSCC was 600,000 and the death recorded from this cancer was 300,000 (1, 2). These incidence and mortality of HNSCC are higher in low- and middle-income countries (LMICs) due to ineffective prevention strategy, late screening, and sub-optimal diagnostic and therapeutic tools (3). According to the World Bank, 71% (41/98) of the LMICs are in Africa (World Bank 2017). There has been reports of dissimilarities in genetic aetiology of cancer based on ethnic differences in mutations (3). Considering their more genetic diversity, characterisation of polymorphism in African HNSCC, may result in the identification of molecular targets associated with the risk of these carcinomas. Studying genetic polymorphism in African cancers may uncover previously unreported HNSCC genetic variants that will help better understand the biology, diagnostic methods and therapy for this disease.